2002
DOI: 10.1192/bjp.180.2.104
|View full text |Cite
|
Sign up to set email alerts
|

Patient adherence in the treatment of depression

Abstract: The studies did not give consistent indications of which interventions may be effective. Carefully designed clinical trials are needed to clarify the effect of single and combined interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
164
3
8

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(191 citation statements)
references
References 38 publications
13
164
3
8
Order By: Relevance
“…Based upon prior studies finding racial differences in various components of depression care, we hypothesized that older African-American subjects would have significantly lower rates of four-month adherence than older white subjects. Consistent with prior work documented in the elderly [19], for the study population as a whole, we found that overall adherence was lower than optimal (approximately 60%). Older African-American adults had significantly lower rates of antidepressant adherence than white older adults in models adjusting for demographic characteristics and symptom variables, but not in models that also included functional status variables.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Based upon prior studies finding racial differences in various components of depression care, we hypothesized that older African-American subjects would have significantly lower rates of four-month adherence than older white subjects. Consistent with prior work documented in the elderly [19], for the study population as a whole, we found that overall adherence was lower than optimal (approximately 60%). Older African-American adults had significantly lower rates of antidepressant adherence than white older adults in models adjusting for demographic characteristics and symptom variables, but not in models that also included functional status variables.…”
Section: Discussionsupporting
confidence: 90%
“…Non-adherence is common, with estimates ranging from 40% to 75% [19]. Thus, even with successful screening and diagnosis of late-life depression in health care settings, a second-generation problem of a “treatment gap”, has emerged.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have documented high rates of discontinuation of antidepressants, 3,[8][9][10][11][12][13][14][15] with one review reporting that between 45 and 60% of patients stop taking prescribed antidepressants within 3 months of beginning treatment. 14 A minimum of six to nine months of pharmacotherapy is recommended for depression treatment after symptoms resolve, 16 17 but given the chronic and recurring nature of most other indications for antidepressants (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] Most of those who do access depression treatment receive it in primary care settings, 9,14,15,19 where antidepressants are the most common form of treatment. However, patient adherence to antidepressants is poor (40%-75%), 20 and many individuals do not consider antidepressants acceptable treatments 21 or prefer to be treated without medication. [22][23][24][25][26] Individuals who are dissatisfied with the availability of conventional treatment, report difficulty getting treatment, or are unable to get treatment are more likely to use CHAs.…”
mentioning
confidence: 99%